2019
DOI: 10.1039/c8an02092b
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric analysis of integrated FTIR and Raman spectra obtained by non-invasive exfoliative cytology for the screening of oral cancer

Abstract: FTIR spectroscopy and Raman spectroscopy of biological analytes are increasingly explored as screening tools for early detection of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…A multivariate statistics algorithm with PCA-LDA analysis was used to analyze the identity between the control group and the three drugs treated groups. This algorithm is widely used in biomedical applications as a powerful spectral analysis method [45][46][47]. The normalized data of the whole Raman spectra was input into the SPSS software for factor analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate statistics algorithm with PCA-LDA analysis was used to analyze the identity between the control group and the three drugs treated groups. This algorithm is widely used in biomedical applications as a powerful spectral analysis method [45][46][47]. The normalized data of the whole Raman spectra was input into the SPSS software for factor analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time; breast cancer biopsy data was explored using AI and ML approaches based on subtype classification. AI approach studies have identified malignant tissues from normal and benign in various cancers such as lung cancer [54,60], skin cancer [61,62], brain cancer [18,63], gastro intestinal cancer [64,65], and oral cancer [66].…”
Section: Discussionmentioning
confidence: 99%
“…A step-wise increase in the MN index was observed from the control population to the pre-cancer patients to the cancer patients by 1.14 to 2.63 to 4.88, respectively [ 106 ]. In a recent study by Ghosh et al, Raman and FTIR data of exfoliated cells were used to distinguish the stages of oral cancer [ 107 ]. Few other spectroscopic methods used to detect the oral malignancy are elastic scattering spectroscopy [ 25 ], diffuse reflectance spectroscopy [ 22 ], and optical coherence tomography [ 44 ].…”
Section: Techniques Used For Diagnosis Of Oral Cancermentioning
confidence: 99%